Axial Turbo-Expander Design for Organic Rankine Cycle Waste-Heat Recovery With Comparative Heavy-Duty Diesel Engine Drive-Cycle Performance Assessment - Soldado, Juan Carlos; Pesyridis, Apostolos; Sphicas, Panos; Nikolakopoulos, Pantelis; Markides, Christos N.; Deligant, Michael (Frontiers in Mechanical Engineering, 2021)
Despite the high thermal efficiency achieved by modern heavy-duty diesel engines, over 40% of the energy contained in the fuel is wasted as heat either in the cooling or the exhaust gases. By recovering part of the wasted energy, the overall thermal efficiency of the engine increases and the pollutant emissions are reduced. Organic Rankine cycle (ORC) systems are considered a favourable candidate technology to recover exhaust gas waste heat, because of their simplicity and small backpressure impact on the engine performance and fuel consumption. The recovered energy can be transformed into electricity or directly into mechanical power. In this study, an axial turbine expander for an ORC system was designed and optimized for a heavy-duty diesel engine for which real-world data were available. The impact of the ORC system on the fuel consumption under various operating points was investigated. Compared to an ORC system equipped with a radial turbine expander, the axial design improved fuel consumption by between 2% and 10% at low and high engine speeds. Finally, the benefits of utilising ORC systems for waste heat recovery in heavy-duty trucks is evaluated by performing various drive cycle tests, and it is found that the highest values of fuel consumption were found in the NEDC and the HDUDDS as these cycles generally involve more dynamic driving profiles. However, it was in these cycles that the ORC could recover more energy with an overall fuel consumption reduction of 5% and 4.8%, respectively.